Communication as Therapy: The Role of Interpersonal Interaction in Reducing Stress Among College Students - Farid Aji Prakosa; Noor Afy Shovmayanti; Azzahrah Miftahul Jannah (the Faculty of Education and Teacher Training of the Institut Agama Islam Negeri (IAIN) Langsa, 2024)
This study examines the therapeutic role of interpersonal communication in addressing mental health challenges college students face. This study employs a qualitative descriptive approach, involving in-depth interviews with students to examine the therapeutic role of interpersonal communication in addressing mental health challenges. The findings reveal that interpersonal communication, both with peers and family, serves as a primary support mechanism for alleviating stress and anxiety. Emotional support gained through these interactions fosters social connectedness and emotional relief and aids students in managing academic and personal pressures. However, privacy concerns often pose significant barriers. The study highlights the importance of creating supportive communication environments to enhance the therapeutic potential of interpersonal communication as an informal tool for addressing mental health challenges.